Analysis of Dietary Abstinence in Madeung Culture against Wound Healing in Post-Partum Mothers Perineum in the Working Area of Samadua Health Center - Sri Rosita; Rahmayani Rahmayani; Diza Fathamira Hamzah (International Conference on Multidisciplinary Research, 2022)
Madeung is one of the traditions of the people of Aceh, especially the people in the Samadua sub-district, in caring for post-partum mothers by abstaining from eating during the post-partum period. This abstinence from eating behavior has an impact on the mother's health, namely a lack of nutrition which results in slow healing of perineal wounds. This study aims to analyze the behavior of abstinence from eating madeung culture in healing perineal wounds in post-partum mothers in Samadua District. This study uses a design using a combination method or Mixed Methods with the Concurrent Embedded model. The sample of this research was 45 post-partum mothers using purposive sampling technique. Data analysis was performed using the chi square test. The results of the study showed that there was a significant relationship between food restrictions and perineal wound healing with a p-value of 0.001 with a 95% confidence interval. It can be concluded that Ha is accepted and H0 is rejected. The results of the qualitative analysis show that abstinence from eating, which is believed so far, can slow down the healing of perineal wounds because the mother lacks nutrition, which has an impact on the health of the mother and baby. Postpartum mothers are advised not to abstain from eating during the postpartum period because it can slow down the healing of perineal wounds and to health workers. especially village midwives to provide special assistance to postpartum mothers intensely and provide information related to dietary restrictions that are detrimental to health. Keywords: Madeung Culture, Abstinence Eating, Perineal Wound